The Odd Harmonious Labeling on Variation of the Double Quadrilateral Windmill Graphs - Firmansah, Fery (Jurnal ILMU DASAR, 2017)
A Graphis calledif it hasvertices and edqes. The graphis said to be an odd harmonious if there exists an injectionsuch that induced mappingis a bijection and is said to be an odd harmonious labeling of. In this paper, we construct the odd harmonious labeling on variation of the double quadrilateral windmill graph with . Moreover, we also give odd harmonious labeling construction for generalized variation of the double quadrilateral windmill graph withand . Keywords: Odd harmonious labeling, variation, double quadrilteral, windmill graph.